Secular trends and social inequalities in child behavioural problems across three Brazilian cohort studies (1993, 2004 and 2015). (17th April 2023) - Degli Esposti, Michelle; Matijasevich, Alicia; Collishaw, Stephan; Martins-Silva, Thaís; Santos, Iná S.; Baptista Menezes, Ana Maria; Domingues, Marlos Rodrigues; Wehrmeister, Fernando C.; Barros, Fernando; Murray, Joseph
Abstract: Aims: Previous epidemiological evidence identified a concerning increase in behavioural problems among young children from 1997 to 2008 in Brazil. However, it is unclear whether behavioural problems have continued to increase, if secular changes vary between sociodemographic groups and what might explain changes over time. We aimed to monitor changes in child behavioural problems over a 22-year period from 1997 to 2019, examine changing social inequalities and explore potential explanations for recent changes in behavioural problems between 2008 and 2019. Methods: The Child Behaviour Checklist was used to compare parent-reported behavioural problems in 4-year-old children across three Brazilian birth cohorts assessed in 1997 (1993 cohort, n  = 633), 2008 (2004 cohort, n  = 3750) and 2019 (2015 cohort, n  = 577). Response rates across all three population-based cohorts were over 90%. Moderation analyses tested if cross-cohort changes differed by social inequalities (demographic and socioeconomic position), while explanatory models explored whether changes in hypothesized risk and protective factors in prenatal development (e.g., smoking during pregnancy) and family life (e.g., maternal depression and harsh parenting) accounted for changes in child behavioural problems from 2008 to 2019. Results: Initial increases in child behavioural problems from 1997 to 2008 were followed by declines in conduct problems (mean change = −2.75; 95% confidence interval [CI]: −3.56,  −1.94; P  < 0.001), aggression (mean change = −1.84; 95% CI: −2.51,  −1.17; P  < 0.001) and rule-breaking behaviour (mean change = −0.91; 95% CI: −1.13, −0.69 P  < 0.001) from 2008 to 2019. Sex differences in rule-breaking behaviour diminished during this 22-year period, whereas socioeconomic inequalities in behavioural problems emerged in 2008 and then remained relatively stable. Consequently, children from poorer and less educated families had higher behavioural problems, compared to more socially advantaged children, in the two more recent cohorts. Changes in measured risk and protective factors partly explained the reduction in behavioural problems from 2008 to 2019. Conclusions: Following a rise in child behavioural problems, there was a subsequent reduction in behavioural problems from 2008 to 2019. However, social inequalities increased and remained high. Continued monitoring of behavioural problems by subgroups is critical for closing the gap between socially advantaged and disadvantaged children and achieving health equity for the next generation.